PURIFICATION AND PARTIAL CHARACTERIZATION OF A GLYCOPROTEIN WITH AMIDOLYTIC ACTIVITY OBTAINED FROM SNAKE VENOM BOTHROPS BARNETTI - Inga A., R. (2010)
A glycoprotein from the venom of Bothrops barnetti snake , was purified using gel filtration and ionic exchange chromatography . This protein showed 48 kDa as molecular weight by PAGE-SDS under nonreducing conditions being its carbohydrate content 48% of the total mass protein. This enzyme had activity either Benzoil Arginil-p-Nitroanilide (BApNA) and human citrated plasma. In addition this enzyme was strongly inhibited by PMSF and tripsin soybean inhibitor indicating that it is a seninoproeinase